2021
DOI: 10.1021/acs.macromol.0c02708
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Thermoresponsive Molecular Brushes as Nanoreactors for Asymmetric Aldol Addition in Water

Abstract: The manipulation and tunability of self-assembled block copolymers through external stimuli present an attractive strategy to develop smart polymer-based nanoreactors as supports for non-orthogonal tandem catalysis. We report on thermoresponsive core−shell micelles based on poly[norbornene-poly(2-methyl-2-oxazoline-block-2-propyl-2-oxazoline)]-graf tpoly[norbornene L-proline] (P[NB-P(MeOx-b-PropOx)]-graft-P[NB-L-proline]) as catalyst supports for L-proline. These molecular brushes exhibit large differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 77 publications
0
26
0
1
Order By: Relevance
“…Living ring-opening metathesis polymerization (ROMP) is one of the most powerful methods for synthesizing well-defined amphiphilic block polymers with controlled molecular weights (MW) and low dispersities ( Đ ). , The sequential ROMP of norbornene-based monomers following the “grafting-through” strategy is an effective methodology for the preparation of highly branched amphiphilic brush copolymers (also known as molecular brushes or bottlebrush copolymers) with unique self-assembly, drug delivery, and imaging capabilities. , This is possible due to the exceptional functional group tolerance of highly active Grubbs initiators and the mild reaction conditions required …”
Section: Introductionmentioning
confidence: 99%
“…Living ring-opening metathesis polymerization (ROMP) is one of the most powerful methods for synthesizing well-defined amphiphilic block polymers with controlled molecular weights (MW) and low dispersities ( Đ ). , The sequential ROMP of norbornene-based monomers following the “grafting-through” strategy is an effective methodology for the preparation of highly branched amphiphilic brush copolymers (also known as molecular brushes or bottlebrush copolymers) with unique self-assembly, drug delivery, and imaging capabilities. , This is possible due to the exceptional functional group tolerance of highly active Grubbs initiators and the mild reaction conditions required …”
Section: Introductionmentioning
confidence: 99%
“…This was attributed to enhance hydrophobic effect of the norbornene backbone. 96 On the contrary, it was also demonstrated that increasing molecular weight of poly(N,N 0 -dimethyl(methacryloylethyl) ammonium propanesulfonate) (PDAMPS) gives rise to higher UCST. This could be explained by considering the increasing inter-chain interactions due to the increasing number of charged pendants.…”
Section: Molecular Weight and Polymer Concentrationmentioning
confidence: 99%
“…22a). 96 Furthermore, instillation of the nanoreactors could enable temperatureassisted recyclability to soluble catalysts. Two works published in 2019 illustrated that providing ethylene glycol-based polymers as scaffolds maintained high catalytic activity, in comparison to soluble catalysts, while became recoverable simply by precipitation using additional heat.…”
Section: Controlled Catalysismentioning
confidence: 99%
“…The yield decreased with every reuse, and selectivity decreased after the third reuse. The apparent decrease in catalytic efficiency and selectivity was attributed to the loss of micelles and disruption of the micelle structure during extraction [ 85 ]. The performance of micellized block copolymers was compared to that of random copolymers that to did not form micelles.…”
Section: Block Copolymer Micellesmentioning
confidence: 99%